Pregnancy-Adapted YEARS Algorithm for Diagnosis of Suspected Pulmonary Embolism. Issue 3 (September 2019) - van der Pol, L.M.; Tromeur, C.; Bistervels, I.M.; Ni Ainle, F.; van Bemmel, T.; Bertoletti, L.; Couturaud, F.; van Dooren, Y.P.A.; Elias, A.; Faber, L.M.; Hofstee, H.M.A.; van der Hulle, T.; et al.
Abstract : ( N Engl J Med . 2019;380(12):1139–1149. Doi:10.1056/NEJMoa1813865) Pregnancy and venous thromboembolism (VTE) share many symptoms and physiological changes, presenting a challenge for VTE diagnosis in pregnant women. The threshold for testing pregnant women for pulmonary embolism is low, as this population is at higher risk for VTE and fatal pulmonary embolism. While some studies have examined the practice of ruling out pulmonary embolism in pregnant women without imaging tests (only using decision rules or D-dimer tests), there is a lack of international consensus regarding diagnostic approaches for pulmonary embolism during pregnancy. The YEARS study showed a low incidence of diagnostic failure when using the YEARS diagnostic algorithm in men and women. This study aimed to evaluate a pregnancy-adapted version of the YEARS algorithm for the management of suspected pulmonary embolism during pregnancy.